Hypomagnesaemia linked to depression: a systematic review and meta‐analysis. Issue 4 (April 2015) - Cheungpasitporn, W.; Thongprayoon, C.; Mao, M. A.; Srivali, N.; Ungprasert, P.; Varothai, N.; Sanguankeo, A.; Kittanamongkolchai, W.; Erickson, S. B.
Abstract Background The reported risk of depression in patients with hypomagnesaemia is controversial. Aim The objective of this meta‐analysis was to assess the association between depression and hypomagnesaemia. Methods A literature search was performed using MEDLINE, EMBASE, Cochrane Database and clinicaltrials.gov from inception through October 2014. Studies that reported odds ratios, relative risks or hazard ratios comparing the risk of depression in patients with hypomagnesaemia were included. Pooled risk ratios (RR) and 95% confidence interval (CI) were calculated using a random‐effect, generic inverse variance method. Results Six observational studies (three cohort studies, two cross‐sectional studies and a case–control study) with a total of 19 137 patients were identified and included in the data analysis. The pooled RR of depression in patients with hypomagnesaemia was 1.34 (95% CI, 1.01–1.79, I2 = 33%). The association between depression and hypomagnesaemia was marginally insignificant after the sensitivity analysis including only cohort and case–control studies, with a pooled RR of 1.38 (95% CI, 0.92–2.07, I2 = 24%). Conclusion Our study demonstrates a potential association between hypomagnesaemia and depression. Further studies assessing the benefits of treatment of hypomagnesaemia in patients with depression are needed.